1999
DOI: 10.1016/s0014-5793(99)00152-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical distribution and functional characterization of an organic anion transporting polypeptide 2 (oatp2)

Abstract: The rabbit polyclonal antibody against rat organic anion transporting polypeptide 2 (oatp2) was raised and immunoaffinity-purified. Western blot analysis for oatp2 detected two bands ( 74 and 76 kDa) in rat brain and a single band (76 kDa) in the liver. By immunohistochemical analysis, the oatp2 immunoreactivity was specifically high at the basolateral membrane of rat hepatocytes. Functionally, the oatp2-expressing oocytes were found to transport dehydroepiandrosterone sulfate, delta1 opioid receptor agonist [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 19 publications
5
45
0
Order By: Relevance
“…37) Organic anion-transporting polypeptide2 (oatp2) protein has been cloned 38,39) and detected in rat liver hepatocytes, brain capillary endothelial cells, and the choroid plexus epithelial cells, suggeting that it plays an important role in the disposition of some drugs. [40][41][42] Although oatp2 is located at the BBB, it is not yet clear whether oatp2 is involved in the influx or efflux transport of organic anions at the BBB. TM-BBB cells exhibit a concentration-dependence for dehydroepiandrosterone sulfate (DHEAS), a neuroactive steroid 43) and a substrate for oatp2, 42,44) and the cell has a K m of 34.4 mM.…”
Section: Transport Characterization Of Condition-ally Immortalized Cementioning
confidence: 99%
“…37) Organic anion-transporting polypeptide2 (oatp2) protein has been cloned 38,39) and detected in rat liver hepatocytes, brain capillary endothelial cells, and the choroid plexus epithelial cells, suggeting that it plays an important role in the disposition of some drugs. [40][41][42] Although oatp2 is located at the BBB, it is not yet clear whether oatp2 is involved in the influx or efflux transport of organic anions at the BBB. TM-BBB cells exhibit a concentration-dependence for dehydroepiandrosterone sulfate (DHEAS), a neuroactive steroid 43) and a substrate for oatp2, 42,44) and the cell has a K m of 34.4 mM.…”
Section: Transport Characterization Of Condition-ally Immortalized Cementioning
confidence: 99%
“…Oatp1 is expressed, in addition to the sinusoidal membrane of hepatocytes [9], in the apical membrane of the proximal tubule [10] and in the apical membrane of the choroid plexus [11]. Oatp2 protein was detected in rat liver hepatocytes, endothelial cells of the blood\brain barrier [12][13][14] and the choroid plexus [12]. On the basis of Northern-blot analysis, Oatp3 is expressed in the kidney, liver and the retina [4].…”
Section: Introductionmentioning
confidence: 99%
“…One of the problems associated with the inability of many peptides and proteins to accumulate in the brain in therapeutically meaningful amounts is the efflux transport systems. For example, it has been shown that the selective ␦-opioid receptors against [D-Pen 2 ,D-Pen 5 ]-enkephalin (DPDPE) has a poor BBB permeability that is explained in part by P-glycoprotein (P-gp)-mediated efflux, and DPDPE is also a substrate of the rat organic anion transporting polypeptide 2 (OATP2) and human OATP-A (Kakyo et al, 1999;Gao et al, 2000).To overcome the limited access of drugs to the brain, various strategies have been applied to direct central nervous system (CNS) drugs into the brain . Most of these methods are invasive, such as surgical implantation of an intraventricular catheter followed by drug infusion into the ventricular compartment, transient opening of the tight junctions by the intracarotid infusion of a hypertonic solution (Chamberlain et al, 1993;Kroll and Neuwelt, 1998;Temsamani et al, 2000), or intracarotid arterial infusion of vasoactive substances such as bradykinin or bradykinin analogs (Bartus et al, 1996).…”
mentioning
confidence: 99%
“…One of the problems associated with the inability of many peptides and proteins to accumulate in the brain in therapeutically meaningful amounts is the efflux transport systems. For example, it has been shown that the selective ␦-opioid receptors against [D-Pen 2 ,D-Pen 5 ]-enkephalin (DPDPE) has a poor BBB permeability that is explained in part by P-glycoprotein (P-gp)-mediated efflux, and DPDPE is also a substrate of the rat organic anion transporting polypeptide 2 (OATP2) and human OATP-A (Kakyo et al, 1999;Gao et al, 2000).…”
mentioning
confidence: 99%